STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI SISWA TUNAGRAHITA DI SEKOLAH MENENGAH PERTAMA LUAR BIASA NEGERI PEMBINA TINGKAT PROVINSI SUMATERA UTARA - Fitty Usda Etika Panjaitan (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2017)
ABSTRAK: The purpose of the research is to determine the procedure, strategies, methods, evaluations,media and the obstacles of application of the Islamic religious teaching for the special educationneed students, particularly the retarded ones, at the state school of the special education needstudents namely SMPLB PTP Sumatera Utara. Their inability to proceed the lesson, resulting fromtheir below average intellectual capacity, has become an attention. Therefore, they need to have adifferent approach compared with the normal ones.The research implements a qualitative descriptive analysis. The resources of the research are theteacher of the Islamic subject, the administration staff and the parents while the data collectiontechnique is done through observation, interview and the document review. Using Miles’ and Huberman’squalitative data analysis interactive model, the data analysis technique conducted simultaneouslywith the process of data collection. It covers the reduction of the data, the display of the data and thedrawing of the conclusion or verification.The findings of the study or research are six: (1) The procedure of the Islamic religion teaching ( PAI) isdone by materialpreparation, presentation of prayer material, connecting material with daily life, summarizingthe material, and applying prayer in the daily life of the students. (2) Learning strategy of PAI is expositoryand contextual strategy on cognitive aspect, VCT strategy (value clarification technique) on affectiveaspect, and direct learning strategy on psychomotor aspect. (3) PAI learning method is lecture method,question-answer method, method of demonstration and exemplary method. (4) The media of PAIlearning is the praying equipment, namely sarong (sheath), the veil, and prayer mats. (5) The evaluationof PAI learning is by test and non-test techniques. The test technique is written test and oral test. Whilenontes technique that is with observation. (6) The learning obstacles of PAI are the limitations ofstudents in remembering the lesson, the limited ability of students’ language, the lack of discipline ofstudents in the school entrance, and the absence of companion teachers.Kata kunci: Strategi pembelajaran, Pendidikan Agama Islam, siswa tunagrahita.